Lifelong learning for music teachers in the face of the challenges of today’s society: what does educational policy offer us? A Qualitative research - Blanco García, Yurima; Serrano Pastor, Rosa María (Revista Complutense de Educación, 2025)
The professional development of music teachers is essential to meet the needs and challenges of 21st century education. Despite its importance, there are few studies on this subject in Spain. The aim of this article is to examine how educational policies are reflected in the teacher professional development (TPD) of music teachers in Spain, analyzing whether they respond to the needs and challenges identified by music teachers in compulsory education. A qualitative methodology is used, including documentary analysis, case studies and life stories. Four categories provided by the project (anonymized) were used for the interviews. Three emerging categories of analysis were identified: ensuring lifelong learning, ensuring the provision of key aspects and promoting the diversity of training modalities. The results show the need for a change in educational policy, taking into account the vision of the teachers themselves. In the context of the implementation of a new education law (LOMLOE), it is necessary to study, reflect and adopt different actions to guarantee a quality TPD for all teachers, which will have an impact on their competence development and the results of educational success.